2017
DOI: 10.5194/nhess-17-2313-2017
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of social vulnerability to natural hazards in Nepal

Abstract: Abstract. This paper investigates district-wide social vulnerability to natural hazards in Nepal. Disasters such as earthquakes, floods, landslides, epidemics, and droughts are common in Nepal. Every year thousands of people are killed and huge economic and environmental losses occur in Nepal due to various natural hazards. Although natural hazards are well recognized, quantitative and qualitative social vulnerability mapping has not existed until now in Nepal. This study aims to quantify the social vulnerabil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 31 publications
0
23
0
1
Order By: Relevance
“…In this category, methods assess preparedness, coping and adaptive capacity of vulnerability based on the fabric of society. A wide range of factors may be considered as an effective cause of vulnerability, but it should be noted that there is no generally accepted methodology that includes all aspects of social vulnerability [40]. It should be noted that the assessment of social vulnerability based on indicator-based methods is very important and practical.…”
Section: Resultsmentioning
confidence: 99%
“…In this category, methods assess preparedness, coping and adaptive capacity of vulnerability based on the fabric of society. A wide range of factors may be considered as an effective cause of vulnerability, but it should be noted that there is no generally accepted methodology that includes all aspects of social vulnerability [40]. It should be noted that the assessment of social vulnerability based on indicator-based methods is very important and practical.…”
Section: Resultsmentioning
confidence: 99%
“…The level of vulnerability of the community in every village is diverse. Another research [15] stated that community vulnerability was determined based on 13 indicators just based on census data. In this study only two indicators were used, namely physical vulnerability (estimated number of houses, number of public facilities) and social vulnerability (population density, vulnerable groups), which in this study were not only based on census data but also direct field survey results so that could be known as the level of community vulnerability in more detail.…”
Section: Community Vulnerability To Landslidesmentioning
confidence: 99%
“…Understanding which different locations and socioeconomic groups are exposed to these hazards and why they are of critical strategic importance, though there is absence of a robust vulnerability mapping and multihazard risk assessment in Nepal, undermines the effectiveness of DRM responses (Gautam 2017).…”
Section: Exposure To Shocks In Nepalmentioning
confidence: 99%
“…Socioeconomic exposure. Gautam (2017) maps social vulnerability 1 and exposure to disasters in Nepal and finds a quarter of all districts rate as either very high (6 districts) or high (18 districts) in terms of vulnerability to disasters. It is suggested that differences in regional HDI and the influence of who had access and control over productive resources play a significant role in determining who is affected by hazards.…”
Section: Exposure To Shocks In Nepalmentioning
confidence: 99%